DAMPAK CORPORATE SOCIAL RESPONSIBILITY, KEPEMILIKAN MANAJERIAL, INVESTMENT OPPORTUNITY SET DAN CASH HOLDING TERHADAP NILAI PERUSAHAAN PADA BANK UMUM SWASTA - TRI WIJAYA, INDRIASID (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract: The purpose of this study wast determine the effect Corporate Social Responsibility (CSR), managerial ownership, Investment Opportunity Set (IOS) and cash holding in the company private national banks listed on the Indonesian Stock Exchange (IDX) from 2008-2012. Population used in this study are all publicly traded companies listed on the IDX. This study used purposive sampling method, with a population of 26 companies and a sample of 9 companies. Criteria used in determining sample of companies listed on the IDX 2008-2012.The analysis technique used in this study is a classic assumption test and t-test statistics fortesting the partial regression coefficients. Results showed that CSR, cash holding does not affect the value of the company. Managerial ownership negatively affect the value of the company. IOS a positive effect on the value of the company. Keywords: CSR, managerial ownership, IOS, cash holding and firm value.